ENHANCING THE EFFICIENCY OF SUPERVISION IN THE CONTEXT OF BANKING RESTRUCTURING - Мамедов , Сергій (Socio-economic relations in the digital society, 2019)
The article explores the importance and role of financial supervision in ensuring the stability of banks and the prevention of crisis phenomena in the banking sector, examines the main models of supervisory systems for the financial sphere, as well as the directions for improving the supervision of banks in the context of restructuring processes. The author proposes a sequence of supervision in the restructuring process in view of the bank’s life cycle, which will allow the optimal distribution of powers between supervisors, avoid duplication of their functions and organize supervision in joint working groups in such a way as to ensure the proper efficiency of the restructuring processes. Proceeding from the necessity to regulate the interaction processes between the National Bank of Ukraine and the Fund for the Guaranteeing of Individuals’ Deposits in the course of the restructuring of banks, ensuring effective supervision and the formation of a proper system of anti-crisis adaptation of banks, the directions of coordination of actions and cooperation between them are provided by providing mutual access to information.